Comparative analysis od thermoelectric energy converters with permeable and solid thermoelements - Anatychuk, L.I.; Vikhor, L.M.; Kotsur, M.P.; Kuz, R.V.; Cherkez, R.G. (Journal of Thermoelectricity, 2021)
The paper describes methods for calculating the optimal parameters of two models of a thermoelectric converter in the mode of electrical energy generation, namely, a sectional converter with the heat carrier movement along the heat-absorbing junctions of thermoelements and a converter of permeable thermoelements, in which the heat carrier passes through channels located along the height of the thermoelement legs. The energy and economic indicators of such models are calculated and their comparative analysis is carried out. Bibl. 32, Fig. 10, Table. 1.